Library Consortia in United Arab Emirates: An Opinion Survey / KN Sheshadri, D Shivalingaiah, K Manjunatha, - KN, Sheshadri; D, Shivalingaiah; K, Manjunatha (2011)
In this paper, the authors attempted to understand the perception of Library and Information Science (LIS) professionals towards the consortia of Libraries in United Arab Emirates (UAE). The research team attempted to explore the notions that are prevailing among the LIS professionals in UAE towards consortium and development of the same in the region. Researchers explored the attitude of LIS professionals towards scope and functions of consortia, nature of resources that can be shared among the members of consortia. It also attempted to understand the possibility of initiating the consortium and identify the thrust areas of cooperation and resource sharing, which might benefit the member libraries. The study was conducted with an overall objective of understanding the perceptions of LIS professionals towards the formation of consortium in UAE. The specific objectives of the study are (i) to understand the attitude of LIS Professionals towards library consortium, (ii) to gather their opinion in developing the consortium in UAE, (iii) to identify the thrust areas for resource sharing and networking and (iv) to suggest the areas that need attention of LIS professionals in developing a consortium. In order to meet the objectives of the study, the authors considered the libraries attached to the universities and institutions those are offering Undergraduate (UG) & Postgraduate (PG) level courses in Medicine, Technology, Management and Humanities / Social Sciences in UAE. While searching DubaiFAQ website, the authors identified 81 institutions in UAE that can be considered as target population for the study. Searching of websites of individual institutions and contacting few individual librarians provided contact details of 91 LIS professionals working in these institutions. As the researchers were desirous to have comprehensive viewpoints from the target population, they considered all the 91 LIS professionals for the study. Personal discussions were held with fellow LIS professionals and existing leading consortia models were examined for obtaining the inputs for designing the survey instrument. The web-based instrument was sent to the target population for responses and follow-up was made with repeated reminders. Out of 91 respondents, the study received 71 responses resulting in 72.8% of response rate. It is observed that about 80% of the LIS professionals did feel that there is a strong need for establishing a consortium of libraries in UAE. About 86% of respondents agreed that the functions of consortium cross the boundaries of library resource sharing to cover the other areas of cooperation. Overwhelming majority of respondents (95.8%) opined that the consortium helps in subscribing online databases and print journals at discounted rates. A majority of them (91.5%) felt that it would facilitate pooling journals among libraries in the region and helps in negotiating with vendors for higher discounts (84.5%). A majority of the respondents (93.0%) expressed that the consortium helps in combined collection development and 91% of them did feel that their authorities will support such movement for an effective collaboration. The paper attempted to identify the factors those influences the functioning of consortia and present some more interesting results.